CD4+CD25+Foxp3+IFNγ+ Treg are immunosuppressive in vitro and increase with intensity of the alloresponse in pretransplant MLC - Daniel, Volker; Sadeghi, Mahmoud; Wang, Haihao; Opelz, Gerhard (Transplant immunology, 2012)
IFNγ-producing CD3+CD4+CD25+Foxp3+ induced Treg are more frequently detectable in patients with good than in patients with impaired long-term kidney graft function. We investigated the in-vitro function of separated CD3+CD4+CD25+Foxp3+IFNγ+ PBL that were induced by phorbol-12-myristate-13-acetate(PMA)/Ionomycin or alloantigenic stimulation. Additionally, we studied iTreg induction and cell proliferation in MLC with pretransplant obtained PBL.